EFEKTIVITAS MINUM JAMU (RAMUAN DAUN KATUK, KUNYIT, LEMPUYANGAN, ASEM JAWA)TERHADAP PRODUKSI ASI PADA IBU NIFAS - Ahmad Baequny; Supriyo .; Sri Hidayati (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2016)
Breast milk is the best food for babies than formula or other. However, in some nursing mothers, breastfeeding expenditure inhibited so not smooth. Traditional herbal medicine is herbal, which is used by postpartum mothers who are believed to facilitate breastfeeding. This study aimstofind out The Effect of the habit of Drinking Herbal (Herb Katuk Leaves, Turmeric, Lempuyangan, Tamarind)On Postpartum Mothers to Breast milk production Region II District Health Center Buaran Pekalongan. Correlative descriptive study design with cross sectional approach. The sampling technique using sample random sampling with 89 respondents. Data collection tool uses a questionnaire to test Chi square. The result showed the majority (77.5%) postpartum mother has a habit of drinking herbal, most (70.8%) milk production postpartum mothers in the current category.Results of statistical test by using Chi-Square test obtained ρ value of 0.001 (<0.05), this result of the study concluded that there is significant Effect of the habit of Drinking Herbal (Herb Katuk Leaves , Turmeric , Lempuyangan , Tamarind)On Postpartum Mothers to Breast milk production Region II District Health Center Buaran Pekalongan. Value CC 0.435 (≠ 0) means that there is a close correlation between drinking herbal on postpartum mother with milk production Region II District Health Center Buaran Pekalongan. RR value of 4,025 can be concluded that postpartum mothers who drink herbal has a chance to smooth milk production by 4 times greater than the postpartum mothers who did not drinkherbal. Suggestions for midwifery personnel are expected to always give health education to mothers postpartum about the medicinal benefits herbal (Herb Katuk Leaves , Turmeric , Lempuyangan , Tamarind)can increase milk production and how to maintain the quality of breast milk.